Size Isn't All that Matters: Noticing Differences in Size and Temporal Order - Wencil, Elaine B.; Radoeva, Petya; Chatterjee, Anjan (Frontiers in Human Neuroscience, 2010)
The ability to represent time and size is essential for thought and action. These domains have traditionally been investigated independently. However, the processing of events in time and space is postulated to have considerable anatomical and behavioral overlap. Here we formally tested for associations and dissociations of abilities in these domains. We examined patterns of impairments in temporal order and relative size judgments in patients with unilateral brain lesions and age-matched control participants. While brain damage can impair both size and temporal order judgments (TOJ), we did not find evidence for global hemispheric differences. When patients were analyzed individually compared to control subjects, we found double dissociations in performances on both kinds of judgments. Voxel lesion symptom mapping allowed us to investigate shared and unique contributions of brain damage to deficits in judgments noticing differences in temporal order and in spatial extent. We found that size and temporal order estimations have overlapping cortical vulnerabilities within the left inferior frontal gyrus, left superior temporal cortex, and bilateral inferior parietal lobule. However, vulnerability unique to TOJ occurred with damage predominantly in left lateralized regions involving inferior and middle frontal cortex and inferior parietal lobule. Conversely, vulnerability unique to size judgments occurred with damage predominantly in right lateralized regions in the supramarginal gyrus and superior temporal cortex. These data provide evidence for interactions between the processing of spatial extent and temporal order; however, they do not provide evidence for right lateralized systems.